A Grey-Fuzzy Multiobjective Model for Supplier Selection and Production-Distribution Planning Considering Consumer Safety. (2nd August 2018) - Memon, Muhammad Saad; Mari, Sonia Irshad; Shaikh, Faheemullah; Shaikh, Shakeel Ahmed
Abstract : Most of the recent product recall incidents indicate that effective management of suppliers and production-distribution planning may play a vital role in increasing product safety. This study explores the opportunities to increase the product safety by analyzing the performance of suppliers and production-distribution system. More precisely, this research analyzes the impact of suppliers' performance on overall profit of supply chain and impact of increasing consumer safety on total profit of supply chain. The novelty of this study is the development of integrated supplier selection and production-distribution model considering consumer risk and product safety. The proposed model is a grey multiobjective model which considers imprecise information as grey parameters. Furthermore, a novel grey-weighted ε -constrained (GWECON) method is developed to solve the proposed multiobjective model.